Membangun Kesadaran Berwarganegara Melalui Keterlibatan Mahasiswa Dalam Program Pembangunan - Miko Harjanti; Sarwititi Sarwoprasodjo (Jurnal Komunikasi Pembangunan, 2016)
The purpose of this article is showing the roles of various parties in a program that involves students with the community.  The contradictory effects will appear on this activity. Society can reap the benefits, in contrary they could also bear the risk of loss. Awhile for the students, these programs allegedly will enrich democratic education as well as raising social awareness. Maximum benefits for both society and student will be obtained through participatory programs, precise potential identification, and appropriate program design according to the necessity of related communities. This activity will also be more synergic with collaboration with the government program.Keywords: civil education, democracy, participation, service learning